An examination of the structural properties and socially constructive aspects of authenticity: A reconsideration of Carl Rogers’ personality theory - Toper, Aydan (2022)
In the last few decades, there has been a surge of interest in the notion of authenticity as a valid variable of individual differences. While research has demonstrated the variable’s association with well-being, Carl Rogers’ personality approach further suggests that people who are deemed to be more authentic are also more socially constructive members of society. As there is minimal research to date on the prosocial and ecological aspects of authenticity, the aim of this work is to examine the structural properties of authenticity, as well as the association with more socially constructive states of being. The results from the four studies undertaken in this study are reported in six chapters. It is shown that there is both a structural similarity and a considerable confluence between the seemingly divergent concepts of authenticity and mindfulness. Authenticity was found to moderate the association between self-compassion and the kindness, common humanity, mindfulness, and indifference subscales of the Compassion Scale. It was also found that authenticity has significant and positive association with self-transcendence, a helping attitude and environmentally considerate behaviour. Self-transcendence was seen to have a mediating effect on the associations between authenticity and the helping attitudes of altruism, receiving and giving. In addition, authenticity was found to be associated with the humility items of openness, self-forgetfulness and focus on others. It was also seen that there is significantly positive correlation between authenticity, forgiveness, and mindfulness, even when social desirability is partialled out. Furthermore, authenticity partially mediates the association between mindfulness and the two subscales of the Heartland Forgiveness Scale: forgiveness of self and forgiveness of situations. Measurement of authenticity, performed across two data sets using Exploratory Factor Analysis followed by Confirmatory Factor Analysis, is perhaps best represented by a two-component model which presents a classification between outer and inner expressions of authenticity.